PENENTUAN TARIF SEWA KAMAR DALAM MENINGKATKAN HUNIAN KAMAR PADA GRAND JATRA HOTEL PEKANBARU - Juika Putri; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The rapid devolopment of hotels in Pekanbaru has resulted in high competitiveness to attract guests to stay at hotels, this makes hotel managers must think of ways to increase the occupancy of hotel rooms the manage. The high competition of hotels in Pekanbaru requires the promotion and management of hotel room facilities that are in line with the hotel star rating. In this case, Grand Jatra Hotel Pekanbaru is one of the hotels that aggressively promotes to increase room occupancy. This study aims to decrible the method of determining room rental rates and describes a strategy of detemining room rental rates in increasing room occupancy at the Grand Jatra Hotel Pekanbaru. This research uses descriptive qualitative method to analyze problems based on interview, observation and documentation data collection techniques wich are then drawn conclusions. The determination of room rental rates includes the methods and startegies used by management in determining room rental rates. From the results of the study, it apprears that the use of methods and strategies is good enough, but there is still a need for increased coorpertion with the govermment.keywords: room rates, method, strategies, occupancy